2017
DOI: 10.1371/journal.pone.0175648
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of human enteropathogenic Yersinia spp. in brown rats (Rattus norvegicus) in Flanders

Abstract: Brown rats (Rattus norvegicus) have been identified as potential carriers of Yersinia enterocolitica and Y. pseudotuberculosis, the etiological agents of yersiniosis, the third most reported bacterial zoonosis in Europe. Enteropathogenic Yersinia spp. are most often isolated from rats during yersiniosis cases in animals and humans, and from rats inhabiting farms and slaughterhouses. Information is however lacking regarding the extent to which rats act as carriers of these Yersinia spp.. In 2013, 1088 brown rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
(55 reference statements)
0
11
1
Order By: Relevance
“…In Italy, Y. pseudotuberculosis O:1 was the most common type identified in wild boar, hare and deer (24). The same type has also newly been identified in brown rats in Belgium (33). Y. pseudotuberculosis O:2, which has more frequently been identified in animals than in humans, was recently reported in Finnish shrews (3,29).…”
Section: Identification Of Yersinia Sppmentioning
confidence: 94%
See 1 more Smart Citation
“…In Italy, Y. pseudotuberculosis O:1 was the most common type identified in wild boar, hare and deer (24). The same type has also newly been identified in brown rats in Belgium (33). Y. pseudotuberculosis O:2, which has more frequently been identified in animals than in humans, was recently reported in Finnish shrews (3,29).…”
Section: Identification Of Yersinia Sppmentioning
confidence: 94%
“…Pathogenic Y. enterocolitica strains have more rarely been identified in wild animals except for wild boars. However, highly pathogenic bioserotype 1B/O:8 has recently been identified in wild rodents in Japan (78) and weakly pathogenic bioserotypes 2/O:5,27 and 3/O:1,2,3 in brown rats in Belgium (33). Non-pathogenic Y.…”
Section: Identification Of Yersinia Sppmentioning
confidence: 99%
“…Pre-baiting is often used in rodent studies (Gurnell 1980;Himsworth et al 2014a;Krojgaard et al 2009;Taylor et al 1974). However, several recently published researches did not employ it (Desvars-Larrive et al 2017; Kajdacsi et al 2013;Panti-May et al 2016Rouffaer et al 2017). Trap success (and/or the assumed neophobic behavior) may also reflect the general availability of food in the vicinity of the traps and low success rate is expected when abundant food is available in or close to the experimental unit (Clapperton 2006).…”
Section: Baitmentioning
confidence: 99%
“…Improvement of the protocol for the cultural detection of Y. pseudotuberculosis. Although cold enrichment in conjunction with alkaline treatment (20 s in 0.25% or 0.5% potassium hydroxide [KOH] solution) has been used in several prevalence studies on Y. pseudotuberculosis (11,(25)(26)(27), some authors reported an increased susceptibility of this species to KOH (28)(29)(30). We analyzed the KOH susceptibility of seven strains belonging to five serotypes (O:1a, O:1b, O:3, O:4, and O:5), some of which are the most common serotypes in Europe (31).…”
Section: Resultsmentioning
confidence: 99%